Development and validation of the Questionnaire of Stressful Life Events (QSLE). (December 2017) - ,; Araya, S.; Arranz, B.; Arteaga, M.; Asensio, R.; Autonell, J.; Baños, I.; Bañuelos, M.; Barajas, A.; Barceló, M.; Blanc, M.; Borrás, M.; et al.
Abstract: Stressful life events (SLEs) are important indicators prior to the onset of first-episode psychosis (FEP). Although there are well-validated interviews and self-reports for assessing SLE on proximate events, unfortunately there are no instruments to assess SLE covering an entire lifetime. This study includes detailed specific items of childhood, adolescence, and adulthood focused on the presence of SLE, emotional impact (stressfulness), and the age at which the event occurred. Our research describes 2 studies designed to develop and validate a new scale to assess SLE: the Questionnaire of Stressful Life Events (QSLE). In Study 1, an over-inclusive item pool was generated based on review of group of experts at Parc Sanitari Sant Joan de Déu and content validity was examined by an Expert Survey. The whole scale represents the content domain. In Study 2, item-level analyses revealed good distributional properties, intra-rater reliability, and convergent and discriminant validity. In the sensitivity and specificity analysis, 18 items had high relevance in the discriminability between patients with FEP and healthy controls. We note that there was an AUC of 0.676, indicating a good predictor. Using 7 as a cutoff to predict an individual as a patient would yield a sensitivity of 64.8% and a specificity of 65%. Overall, the QSLE displayed satisfactory psychometric characteristics in a Spanish population. These results suggest that QSLE gives us the opportunity to investigate childhood, adolescent, and adult life events by measuring the stress and age at the moment on a continuous scale. Highlights: The questionnaire of stressful life events (QSLE) is optimal for psychosis studies. Reliability and validity of QSLE are very satisfactory. The QSLE shows good capacity to discriminate patients and controls. Assess presence and levels of stress helps to understand the impact on psychosis.